2014
DOI: 10.1111/sji.12216
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Alternative exon 7 Splice Variant of the BF Gene and MHC‐Related Marek's Disease Resistance in Chickens

Abstract: The study was to analyse the relationship between the alternative exon 7 splice variant of the BF gene and MHC-related Marek's disease (MD) resistance in chickens. The experiment first determined whether or not the cocks of Xiayan chickens have alternative splicing-out of the exon 7 of the BF gene from peripheral blood leucocytes (PBLs). Then, selected two groups: Group K included the offspring of the selected cocks which have no alternative splicingout of the exon 7 of the BF gene; Group Y included the offspr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Many viral genes in MDV genome have been identified that may involve in MD development, such as, meq [ 47 ], viral telomerase RNA (vTR) [ 48 ], viral interleukin-8 (vIL-8) [ 49 ], phosphoprotein 38 (pp38) [ 50 , 51 ], and MDV miRNAs [ 52 ]. For host genome, some genes involved in MD pathogenies were identified, including MHC [ 27 , 53 ], gga-miR-155 [ 54 ], gga-miR-26a and NEK6 [ 55 ], IGFBP7 and TNFRSF8 [ 39 ]. Several studies also illustrated the mechanism of susceptive or resistance from the epigenomic level [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many viral genes in MDV genome have been identified that may involve in MD development, such as, meq [ 47 ], viral telomerase RNA (vTR) [ 48 ], viral interleukin-8 (vIL-8) [ 49 ], phosphoprotein 38 (pp38) [ 50 , 51 ], and MDV miRNAs [ 52 ]. For host genome, some genes involved in MD pathogenies were identified, including MHC [ 27 , 53 ], gga-miR-155 [ 54 ], gga-miR-26a and NEK6 [ 55 ], IGFBP7 and TNFRSF8 [ 39 ]. Several studies also illustrated the mechanism of susceptive or resistance from the epigenomic level [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also illustrated the mechanism of susceptive or resistance from the epigenomic level [ 56 , 57 , 58 ]. Alternative splicing transcripts were also detected in MD pathogenies [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger central cavity in groove confers substantial conformational flexibility to the crucial residue Arg9, which allows remodelling of key peptide-binding sites and allows peptides with conspicuously different sequences to be bound. This might explain that the exon 7-deprived variant of the BF was detected in MD-susceptible haplotypes, but not in MD-resistant haplotypes [1][2][3].…”
mentioning
confidence: 95%
“…Sample of cDNA extracted from peripheral blood leucocytes (PBL) of Xiayan chickens [2] was used in the experiment. The detailed steps of total RNA isolation and reverse transcription (RT) are described in the previous article [3].…”
mentioning
confidence: 99%